2017
DOI: 10.1021/acs.joc.7b01990
|View full text |Cite
|
Sign up to set email alerts
|

Use of (Cyclopentadienone)iron Tricarbonyl Complexes for C–N Bond Formation Reactions between Amines and Alcohols

Abstract: The application of a series of (cyclopentadienone)iron tricarbonyl complexes to "borrowing hydrogen" reactions between amines and alcohols was completed in order to assess their catalytic activity. The electronic variation of the aromatic groups flanking the C═O of the cyclopentadienone influenced the efficiency of the reactions; however, in other cases, the Knölker catalyst 1, containing trimethylsilyl groups flanking the cyclopentadienone ketone, gave the best results. In some cases, the change of the ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Following this breakthrough, the scope of CIC‐catalyzed amination was expanded to the less reactive benzylic alcohols: Barta and co‐workers achieved this goal optimizing the reaction conditions with CIC 1a (Scheme A), whereas Wills and co‐workers employed the tetraphenyl‐substituted CIC 1g (Scheme B) . The Wills' group later developed a series of new CICs ( 1h–m , Scheme C) and used them in the amination of several substrates, including a few secondary alcohols …”
Section: Applications In Reactions Involving Ht Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this breakthrough, the scope of CIC‐catalyzed amination was expanded to the less reactive benzylic alcohols: Barta and co‐workers achieved this goal optimizing the reaction conditions with CIC 1a (Scheme A), whereas Wills and co‐workers employed the tetraphenyl‐substituted CIC 1g (Scheme B) . The Wills' group later developed a series of new CICs ( 1h–m , Scheme C) and used them in the amination of several substrates, including a few secondary alcohols …”
Section: Applications In Reactions Involving Ht Stepsmentioning
confidence: 99%
“…HB amination of benzylic alcohols promoted by pre‐catalyst 1a (A) and 1g (B) . The CIC series developed by Wills and co‐workers and its application to the HB amination (C) …”
Section: Applications In Reactions Involving Ht Stepsmentioning
confidence: 99%
“…Modifying the structure of the cyclopentadienone moiety, Wills has shown that a catalytic system generated in situ from the modified Knölker complex bearing a tetraphenyl‐pentadienone ligand ( 29 , 10 mol‐%) and Me 3 NO (10 mol‐%) exhibited similar activity when performing the reaction in toluene at 110 °C for 48 h or xylene at 140 °C for 24 h . He also designed a family of (cyclopentadienone)iron tricarbonyl complexes by modulating the electronic properties of the aromatic groups in α ‐positions to the C=O of the cyclopentadienone, and identified the complex 30 as the most active catalyst precursor for the series for BH of alcohols with various amines (10 mol‐% of 30 , 9 mol‐% of Me 3 NO, xylene, 140 °C) . Zhao reported that the complex 31 bearing a benzonitrile ligand instead of a CO (10 mol‐%) in combination with 40 mol‐% of AgF was efficient for the reaction of primary anilines with 5 equiv.…”
Section: Multi‐step Reactions Involving Iron‐catalysed Hydrogen Bomentioning
confidence: 99%
“…Therefore, application of Fe-based catalysts in organic synthesis attract significant attention [34][35][36][37][38][39][40]. Interestingly, iron catalysts were extensively used in cross-coupling reactions, [41][42][43][44][45] hydrogenations and transfer hydrogenations, [46][47][48][49], hydrosilylations [50][51][52], as well as in hydroboration processes [53,54]. However, the application of a Knölker-type complex for the alkylation and methylation of ketones and alcohols is noteworthy [55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%